2008
DOI: 10.1080/09670870701474047
|View full text |Cite
|
Sign up to set email alerts
|

Farmers' knowledge, attitudes, and practices for rodent management in Myanmar

Abstract: A survey of 350 farmers was conducted in the lowland rainfed agricultural system of central Myanmar (Burma) to examine the importance of rodents, farmers' perception of the causes of yield loss, and their beliefs as to why they undertake rodent management. Farmers grew monsoon rice, summer rice and mungbeans with the major constraints upon production identified as pests (29.4% of respondents), followed by insufficient water (19.4%). The main pests were insects (48.6%), followed by rats (40.9%); however, farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…Estimates of annual crop loss and post-harvest contamination by rodents in Africa suggest an extra 200 million people could be fed if such losses could be prevented (Meerburg, Singleton, & Leirs 2009). Farmers often view rodent losses as uncontrollable due to the frequent failure of management activities, particularly in developing countries, which lead to apathy, acquiescence and acceptance of rodent pests in the environment (Posamentier 1997;Singleton et al 1999;Mwanjabe et al 2002;Brown et al 2008). Rapid rodent population expansion caused by biotic and abiotic phenomena has repeatedly led to rodent outbreaks and total crop destruction in many parts of the world (Singleton et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Estimates of annual crop loss and post-harvest contamination by rodents in Africa suggest an extra 200 million people could be fed if such losses could be prevented (Meerburg, Singleton, & Leirs 2009). Farmers often view rodent losses as uncontrollable due to the frequent failure of management activities, particularly in developing countries, which lead to apathy, acquiescence and acceptance of rodent pests in the environment (Posamentier 1997;Singleton et al 1999;Mwanjabe et al 2002;Brown et al 2008). Rapid rodent population expansion caused by biotic and abiotic phenomena has repeatedly led to rodent outbreaks and total crop destruction in many parts of the world (Singleton et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…On a global scale, rodent damage to pre- and post-harvest crops has contributed substantially to malnourishment and reduced food security (Meerburg et al 2009). The damage caused by rodents gnawing on crops can lead to spoilage of stored crops, or structural damage to plants resulting in reduced yields (Elias 1988; Brown et al 2008). Furthermore, close contact between humans and rodents facilitates transmission of rodent-associated human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…At the household level where food is stored, several surveys have shown that rodents are considered a problem, chewing through clothes and blankets, disturbing sleep, biting people and contaminating food stores Garba et al 2013;Stuart et al 2011;Yonas et al 2010). Actions to manage rodents around households often involve keeping a domestic cat, or ad hoc poisoning or trapping (Brown et al 2008;Capizzi et al 2014). Although Langton et al (2001) reported that dwellings with pets had higher numbers of rats and mice in urban habitats in the UK.…”
Section: Introductionmentioning
confidence: 99%